PERILAKU KONSUMSI DAN PRODUKSI KOMUNITAS PENGGEMAR MUSIK VOCALOID DI JEPANG 2008-2012 - Paramita Winny Hapsari; Sudung M. Manurung; Putri Andam (Media Bahasa, Sastra, dan Budaya Wahana, 2018)
AbstractThis thesis discusses about fan culture, as seen from the behavior of consumption, production patterns and fans motivations, especially from the VOCALOID music fans in Japan. VOCALOID is a current phenomenon in Japan, which started since the outbreak of software called Desktop Music. VOCALOID fans have formed large communities that can be called a fandom. The purpose of this study is to analyze the behavior of consumption and production patterns made by commu- nity of VOCALOID music fans as well as their motivation to like the music as a fan culture. This VOCALOID music fans are different from the consumption process as other fans. They are doing some production activities which differ them from other fans. This means that they are an active fans. They are capable of generating the economic value of its own. Their motivation for liking VOCALOID music was influenced by their society circumstances. The motivation of the fans is what brought them together. In accordance with the concept expressed by Henry Jenkins, that the majority of the fans are interested in the minutiae of the object of their fandom and spend most of their time and energy to engage in certain activities commonly conducted by the fandom. Activities undertaken by individuals in this fandom that can be regarded as fan culture.Keyword: consumption; fan culture; Japan; motivation; production; VOCALOID;